Best practice for disable facilities at district mosque / Mohd Aizzat Abdullah and Yuhainis Talib - Abdullah, Mohd Aizzat; Talib, Yuhainis (2020)
Facilities for People with disabilities is one of the important things that need to be considered in designing every public building. People with disabilities shall have the right to enter and use public facilities, utilities, services and buildings accessible. However, if there is no facilities provided, it may threaten the welfare of persons with disabilities. Therefore, this research aims to investigate the best practice for disable facilities for People with Disabilities at District Mosque. The objectives of this research are (i)to identify the type of disabling facilities at district mosque (ii) to analyzes the existing disable facilities, follow standard requirement by Malaysia Standard (iii) to rank disable facilities in Mosque. In order to achieve the objective, an observation has been made at 5 district mosques at Kelantan with the aid of checklist. The result from the observation will analyze based on Malaysian Standard MS1184: 2002. Most of the facilities for disabled people at Kelantan district mosque not fully follow the standard requirement by Malaysian Standard MS1184: 2002. Grab Rail is the best practice disable facilities at district mosque and Mosque A is the best mosque has provided facilities for disable people.